Sparrowhawk (Accipiter nisus) predation on tits (Parus spp.) - Geer, T (1979)
﻿ The present research was conducted to assess the effect of Sparrowhawk predation on the tit population of Wytham Woods, Oxford. Chapter 1 describes the history of the Wytham hawk population until this study began and the nesting biology of the hawks during the study. Six to nine pairs of hawks settled in the wood each year, but reproductive success was low due to pesticide contamination. Chapter 2 shows that tit nesting success was reduced when they nested near hawk nests. Circumstantial evidence is presented for reduced tit nesting success throughout the wood since the return of the hawks. Chapter 3 examines rates of hawk predation during the nesting period. Findings indicate that hunting rates and the percentage of the diet formed by tits are regulated by prey availability or vulnerability, with highest predation rates occurring at the time that tits fledge. In Chapter 4 the selection of tits by hawks is analysed. Results indicate that on the basis of brood and physical characteristics adult tits were selected on the basis of availability and juvenile tits were selected primarily by date of fledging. The ratio of adult to juveniles taken differed between years and was thought to be related to the number of tits available per hawk each year. Chapter 5 presents estimates showing that 22-42% of each segment of the tit population was killed by hawks each year. The effects of these losses are discussed, concentrating on the shift in the structure of the tit breeding population which has occurred since the hawks returned to the wood. In Chapter 6 the findings of the study are compared to the findings of previous predator-prey research and the attributes of Wytham as an area for studying predation discussed.